2006
DOI: 10.1111/j.1600-0870.2006.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of mesoscale low-level winds obtained by dynamical downscaling of ERA40 over complex terrain

Abstract: A B S T R A C TThe mesoscale numerical weather prediction model ALADIN has been applied for downscaling ERA40 data onto a 10 km grid covering the complex terrain of Slovenia. The modelled wind field is compared with the time-series of observations at 11 stations. In addition to traditional scores (root-mean-square error, mean absolute error, anomaly correlation), a frequency-domain comparison is carried out in order to explore aspects of the mesoscale model performance other than that depicted by the conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…Initial and boundary conditions were provided by the global reanalysis of the 40-yr European Centre for Medium-Range Weather Forecasts (ECMWF) ReAnalysis (ERA-40; Kållberg et al 2004), which is available at 125-km grid spacing with a 6-hourly frequency. Following the methods of Beck et al (2004) andŽ agar et al (2006), a direct nesting strategy was implemented. These authors showed that the dynamical downscaling of ERA-40 data with the ALADIN model to ;10-km grid spacing is equally accurate whether or not an intermediate domain is used.…”
Section: Methodsmentioning
confidence: 99%
“…Initial and boundary conditions were provided by the global reanalysis of the 40-yr European Centre for Medium-Range Weather Forecasts (ECMWF) ReAnalysis (ERA-40; Kållberg et al 2004), which is available at 125-km grid spacing with a 6-hourly frequency. Following the methods of Beck et al (2004) andŽ agar et al (2006), a direct nesting strategy was implemented. These authors showed that the dynamical downscaling of ERA-40 data with the ALADIN model to ;10-km grid spacing is equally accurate whether or not an intermediate domain is used.…”
Section: Methodsmentioning
confidence: 99%
“…The initial and boundary conditions necessary to perform the simulation are obtained from a general circulation model. The accuracy of the mesoscale model in representing the wind field can be evaluated by comparing the simulations with independent observational information (e.g., Mahrer et al 1985;Rife et al 2004;Zagar et al 2006). Additionally, hybrid approaches can enhance the spatial resolution of a mesoscale simulation using a diagnostic model (e.g., Ludwig et al 2006); however, their reliability is conditioned to that of the mesoscale simulation and the suitable representation of physical processes.…”
Section: Introductionmentioning
confidence: 99%
“…The value of the WRF simulation should be viewed in the context of the computational costs of running prognostic mesoscale models. Typically, short temporal periods of a few months or specifically the duration of an observational campaign are simulated to limit the computational requirements (Zhong and Fast 2003;Cairns and Corey 2003;Rife et al 2004;Zagar et al 2006). Although the computational power reached in the last years makes multiyear simulations feasible (Buckley et al 2004;Conil and Hall 2006;Walter et al 2006), long simulations at higher spatial resolutions that better capture the details of complex orography and allow for evaluations of variability at longer time scales are still computationally demanding and thus have not been so far extensively used.…”
Section: Introductionmentioning
confidence: 99%
“…This type of model behaviour, which could arise due to the used parameterisations of the model and information about the complex terrain characteristics, has already been observed so far in a large number of modelling studies (e.g. Žagar et al, 2006;Borge et al, 2008;Challa et al, 2009;Papanastasiou et al, 2010).…”
Section: Appendix a Model Verification By The Near-surface Measurementsmentioning
confidence: 99%